Administering socio-economic instruments in crises situations : Examples from Sri Lankan Muslims’ practices - Ameer, U.A. (Faculty of Arts, University of Colombo., 2022)
Crises have become the new normal in today’s world. Social security systems assist individuals, families, and societies in handling conflicts, natural disasters, displacement, and other incidents in a society where crises are happening. It is handled through a range of institutional structures that are suited to each society's needs and are governed by socioeconomic means. This study takes on the conceptual and practical frameworks of institutional administration of social finance instruments in managing crises. Since this study is designed to explore and describe the status of social finance practices of Muslims in Sri Lanka to manage crises situations, it employs several techniques to gather apt data gathered through case studies, field observations, and structured and unstructured interviews to examine expert opinions and referring records related to the practices of Islamic socio-economic instruments such as Islamic crowdfunding, zakat, waqf, interest-free loans in reviving the economy during the crises. And, the gathered data were analyzed using a thematic analysis system to produce handy outcomes. The Islamic socioeconomic instruments comprise: (1) obligatory and charitable wealth redistributive drives like; zakat, sadaqa, waqf, slaughtering, aqeeqah, and crowdfunding, (2) corporate-based instruments like; Qard Hasan, kafala, and (3) trade based Islamic microfinance tools like; Murabaha, salam, ijarah, etc. Most of the above socioeconomic instruments are administered by mosques and some other volunteer organizations belong to Muslim societies. This study may provide some guidance for future planning, strategy, and implementation of appropriate relief measures in crises by Islamic social finance organizations. And, the common experience may encourage others for the common good.
Keywords: Slaughtering; Social protection; Crowdfunding; Zakat; Crises